Predicting the Impact of Chronic Health Conditions on Workplace Productivity and Accidents. Issue 4 (April 2015) - Frey, Jodi Jacobson; Osteen, Philip J.; Berglund, Patricia A.; Jinnett, Kimberly; Ko, Jungyai
<x xml:space="preserve">Abstract</x> Objective: Examine associations of chronic health conditions on workplace productivity and accidents among US Department of Energy employees. Methods: The Health and Work Performance Questionnaire–Select was administered to a random sample of two Department of Energy national laboratory employees (46% response rate; N = 1854). Results: The majority (87.4%) reported having one or more chronic health conditions, with 43.4% reporting four or more conditions. A population-attributable risk proportions analysis suggests improvements of 4.5% in absenteeism, 5.1% in presenteeism, 8.9% in productivity, and 77% of accidents by reducing the number of conditions by one level. Depression was the only health condition associated with all four outcomes. Conclusions: Results suggest that chronic conditions in this workforce are prevalent and costly. Efforts to prevent or reduce condition comorbidity among employees with multiple conditions can significantly reduce costs and workplace accident rates.